Prevalence and risk factors of hand dermatoses among pandan handicrafters - Fajar Waskito, Erni Setiyawati Devi Artami S, Sri AwaliaFebriana, (Universitas Gadjah Mada, 2008)
Background: Pandan handicraft is one of the industrial sectors which has a significant role in employing people in Kulonprogo, Yogyakarta. Development in this industry makes higher material exposure to the hands during the production procedures, that makes it essential to study the risk of suffering from hand dermatoses among the handicrafters.Objective: To determine the prevalence and risk factors of hand dermatoses among pandan handicrafters. Methods: Cross-sectional study was conducted on 80 subjects who was taken randomly from Pandan handicrafter population in Tanjungharjo village, Kulonprogo, Yogyakarta. Prevalence data were analyzed descriptively. Risk factors were analyzed using estimation of prevalence ratio (pr), 95% Confident Interval (el), and chi-square test.Results: Out of 74 subjects fulfilled the criteria, 58 (78.4%) were suffered from hand dermatoses. Callus was the most common disease occurred in 49 (66.2%) subjects, followed by irritant contact dermatitis (lCD) in 18 (24.3%) subjects. History of atopy was proven as risk factor for ICD (p = 0.025, pr = 2.872; 95%el = 0.913-9.032). Types and duration of work were not proven as risk factors, as well as no gloves protection during work.Conclusion: Callus was the most common hand dermatosis occurred among pandan handicrafters, followed by ICD. History of atopy was identified as a risk factor for ICD.Key words : pandan - handicrafter - hand dermatosis - occupational-atopy